EFFICIENCY OF APPLICATION OF COMPLEX TOPICAL DRUGS IN PATIENTS WITH INFLAMMATORY DISEASES OF THE PHARYNX - G. N. Nikiforova; V. M. Svistushkin; D. B. Bidanova; K. B. Volkova (Медицинский совет, 2017)
Infectious-inflammatory diseases of the pharynx are the most common pathological processes in the human population. Correct diagnosis and rational choice of effective treatment are directly correlate with important role of the pharyngeal tube in the life of the organism and a high risk of complications. The vast majority of clinical cases do not require the use of systemic drugs, topical therapy only. However, in the light of new data on the importance of microbial populations (microbiome), working as a functional barrier between the environment and nasopharyngeal mucosa, attention is attracted to topical antiseptics with antiinflammatory and biocenose saving effects, as part of complex therapy in diseases of the throat In the light of this issue, topical drugs based on lysozyme an enzyme, which is a natural antiseptic for the human body, are looking promising. These products are represented by Lysobact®  (Bosnalijek, Bosnia and Hercegovina). It has proven anti-inflammatory, immunomodulatory and antiseptic action, and it`s efficacy is meaningful in treatment of the pharynx diseases in patients of different age groups.